Nikola Vulić’s contribution to the collection and interpretation of ancient inscriptions - Ljubomirović, Irena V. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Judging by his persistence on collecting ancient monuments, Nikola Vulić could be considered as a founder of epigraphic studies on the territory of the former Yugoslavia. Most of inscriptions he has been working on come from the territory of the Former Yugoslav Republic of Macedonia and he analyzed contents of these inscriptions in detail in unpublished manuscript named "Historical contents of our ancient monuments". This and nine more works too were exposed by Nikola Vulić in a period from 1942-1944 and they are still unpublished. Ancient inscriptions help us to research different segments of life of ancient inhabitans on the Balkan Peninsula, and also, to find out about names, geography, language, religion, style of life in Roman period. The research of Nikola Vulić have been not limited with territorial borders - due to his enthusiasm the inscriptions from Serbia, Macedonia, and Bulgaria were incorporated into CIL (Berlin).